Faktor-faktor yang Mempengaruhi Pengungkapan Lingkungan pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2021-2023 - Ulin Nihayah; Naila Najihah (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to examine and analyze the factors that influence environmental disclosure in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period of 2021–2023. The independent variables in this study include environmental performance, environmental management system, proportion of independent commissioners, firm size, firm age, and profitability. Environmental disclosure is measured using the Global Reporting Initiative (GRI) G4 indicators. This research employs a quantitative approach with a sample of 151 manufacturing companies selected using purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that only three out of the six independent variables have a significant influence on environmental disclosure. However, only one of these three—firm age—has a positive direction of influence. This indicates that only one hypothesis is accepted in this study. The coefficient of determination (R²) is 0.328, meaning that 32.8% of the variation in environmental disclosure can be explained by the six independent variables. These findings suggest that internal company factors are not sufficient to fully explain environmental disclosure variations, highlighting the possible influence of external factors such as regulatory pressure or stakeholder expectations.